2023
DOI: 10.3390/healthcare11111611
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physical Activity Patterns among Korean Adolescents during and after COVID-19

Abstract: Due to the COVID-19-induced social distancing restrictions, adolescents’ physical activity declined and their level of health and fitness decreased. In March 2023, the Korean government established the beginning of the post-COVID-19 era by declaring that indoor masks were now “recommended” rather than “mandatory”. Consequently, adolescents, whose physical activity decreased during COVID-19, began to participate in such activities again. This study aimed to verify the differences in adolescent physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…While PA levels in young people have improved now compared to during the pandemic, these improvements were not uniform, and there was a greater recovery in PA levels in older children between the ages of 11 and 16 (Sport England, 2023a). A very recent Korean study of 1143 adolescents reported that the frequency and duration of PA increased after the easing of all COVID-19 restrictions in 2023 compared to during the pandemic (Yun & Lee, 2023), however, it is unclear whether participants have returned to pre-COVID PA levels as the study did not have pre-pandemic baseline data for comparison. Another recent UK study reported that there are still half a million fewer young people between the ages of 16 and 34 who achieve the recommended 150 min of PA per week today compared to 6 years ago (Sport England, 2023a).…”
Section: Information Box 2 Definition and Types Of Pa Included In The...mentioning
confidence: 99%
“…While PA levels in young people have improved now compared to during the pandemic, these improvements were not uniform, and there was a greater recovery in PA levels in older children between the ages of 11 and 16 (Sport England, 2023a). A very recent Korean study of 1143 adolescents reported that the frequency and duration of PA increased after the easing of all COVID-19 restrictions in 2023 compared to during the pandemic (Yun & Lee, 2023), however, it is unclear whether participants have returned to pre-COVID PA levels as the study did not have pre-pandemic baseline data for comparison. Another recent UK study reported that there are still half a million fewer young people between the ages of 16 and 34 who achieve the recommended 150 min of PA per week today compared to 6 years ago (Sport England, 2023a).…”
Section: Information Box 2 Definition and Types Of Pa Included In The...mentioning
confidence: 99%
“…11 A repeated cross-sectional study of Korean adolescents observed higher levels of self-reported physical activity during both school and leisure time post-COVID-19 (April-2023) compared to during-COVID-19 (July-2022). 12 Another prospective study conducted in Sweden that compared the pre-COVID-19 and mid-2021 periods found an increase in SPT while accelerometer-assessed MVPA remained stable when. 13 Considering that the easing of COVID-19 related restrictions occurred at different time points between countries and territories, the evidence from postrestrictions, particularly the opening of schools, is scarce.…”
Section: Introductionmentioning
confidence: 99%